SISTEM INFORMASI PENENTUAN HARGA POKOK PRODUKSI BAJU TAQWA MENGGUNAKAN METODE ACTIVITY BASED COSTING - Kurniawan Wahyu Haryanto (SPIRIT, 2020)
Abstract: One of the garment companies in the city is Nizar Bordir, which produces taqwa clothing with a variety of models and motifs. The company has difficulty in recording raw material costs, labor, factory activities and calculation of cost of production.In determining the cost of production, the writer uses Activity Based Coasting method, focusing on the costs attached to the product based on activities to produce, distribute, or support the product concerned.The information system for determining the cost of production using the Activity Based Costing method can provide information on Cost of Production and can be used as a basis for determining the policy of selling prices of products and knowing the gross profit of a product.Keywords: Information System, Cost of Production, Activity Based Coasting.